Analyzing the Impact of Financial Leverage on ROE and EPS in the Property and Real Estate Sector - Idham Yusri; Nabila Syafiq (Indonesia Accounting Research Journal, 2023)
This research investigates the intricate relationship between financial leverage and two key financial performance indicators, Return on Equity (ROE) and Earnings Per Share (EPS), within the property and real estate industry. By analyzing empirical data and conducting rigorous statistical analyses, this study has unveiled significant insights into the financial dynamics and decision-making processes that govern this dynamic sector. The findings indicate a robust, positive correlation between financial leverage and ROE, reaffirming the notion that judicious employment of debt financing can amplify profitability and returns for shareholders in the property and real estate industry. However, the analysis also reveals that the impact of financial leverage on EPS is more nuanced, reflecting the multifaceted nature of per-share profitability influenced by operational efficiency, market conditions, and industry-specific dynamics. The practical implications of these findings extend to companies, investors, and policymakers within the property and real estate sector. Companies can utilize these insights to optimize their debt structures, manage financial risk, and enhance their attractiveness to investors. These insights offer a roadmap for balanced financial decision-making, enabling companies to strike the right equilibrium between leveraging debt for growth and maintaining financial stability. This research not only contributes to the existing body of literature in corporate finance but also provides industry-specific evidence, fostering a deeper understanding of financial decision-making and its consequences within the property and real estate sector. As this sector continues to evolve, the findings from this study serve as a valuable compass for well-informed and strategic decision-making, enriching our comprehension of financial dynamics and shaping the future of companies, investors, and the industry itself.